Numerical and limit equilibrium stability analyses of cemented mine backfill upon vertical exposure - Yang, PY; Li, L (UMT 2017: First International Conference on Underground Mining Technology, 2017)
In open stope mines, the cemented backfill must maintain self-standing in the primary stope during the extraction of an adjacent secondary stope. A limit equilibrium solution proposed by Mitchell et al. (1982) has been widely used since the 1980s to design the exposed cemented fill. This solution has been the object of several modifications over the years. Recently, the comparison between these solutions and numerical simulations indicated that the former are not fully representative of the exposed fill when its required cohesion is relatively large. In this paper, new numerical results show that the slip surface transitions from planar at low fill cohesion to spoon-shaped at larger cohesion. In the former case, the failure is controlled by shear stresses mobilised along the planar slip surface. This is very similar to the failure mode assumed in existing theoretical models. In the latter case, however, the failure is governed by both shear (near the base) and tensile (near the top) stresses, indicating a different failure mode. Based on these observations, a new analytical solution is proposed to evaluate the stability of side-exposed cemented fill. This solution is validated using complementary simulations and the results indicate that the two different approaches agree well for typical stope geometry and fill properties.
Keywords: exposed mine backfill; Mitchell et al. solution; limit equilibrium; numerical modelling